Factors Influencing Students Intention to Become a Technosociopreneur - Suryowati, Budi; Harianti, Ati; Seftiono, Hermawan (Journal Research of Social Science, Economics, and Management, 2022)
Currently there is a new concept of entrepreneurship that combines technopreneurs and sociopreneurs known as teknosociopreneurship. The terms techno is about technology innovation and industry 4.0. Socio is a social impact on the surrounding community and collaboration. In this study, the characteristics of technosociopreneurs refer to the values of technosociopreneurs embraced by Trilogy University which consists of integrity, togetherness, independence, excellence, and innovation. This study aims to determine the influence of integrity, togetherness, independence, excellence, and innovation possessed by Trilogy University students on their intention to be a techno-sociopreneur. The population used consists of 2,289 students, spread over 12 study programs. From the population, 350 students were obtained by using cluster sampling method. The data analysis used was Partial Least Square - Structural Equation Modeling (PLS-SEM). The result of the study indicate that out of five basic values possessed by Trilogy University students that affect their intention in becoming a techno-sociopreneur are integrity, togetherness, and innovation.